Geomorphological survey at Padang Candi, Kuantan Singingi Regency, Central Sumatra, Indonesia - Johan Arif (Pubawidya: Jurnal Penelitian dan Pengembangan Arkeologi, 2019)
Padang Candi site in the Kuantan Singingi Regency of Riau Province, located about 19.3 km southwest of Taluk city, and about 3 km northeast of Lubuk Jambi. In the year 2000s, some archaeological stuff have been found at Padang Candi, among others, various sized of bricks as a raw material for building construction, and some gold plate with scrip. It is presumed those stuffs had a connection with the Sriwijaya Kingdom between AD 800. The goal of the paper is to gain a spectrum of understanding about the assemblages of bricks as a raw material for building construction was found, on three sites that are at Sector-I (sec-I), and the others in small quantities were found at Sector-II (sec-II) and Sector-III (sec-III) on the basis of geomorphological study. This study involves the geomorphological investigation of the area at the scale of 1:2000. In terms of geomorphology, the landscape at Padang Candi consists of two units, namely, the Floodplain Unit formed by Quaternary river alluvium (Qal), and the Low Hilly Unit composed by Tuff Unit as a part of the Miocene Telisa Formation (Tmtu). Sector-I (sec-I) situated on the relatively higher isolated hilly than sec-II and sec-III. The area westward of sec-II might be remains of ancient settlement, and there is trench-like morphology found eastward of sec-I. In the matter of sec-1 which is situated on isolated hilly, evoke a curiosity about the status of building construction at sec-I. The presence of the trench-like morphology also gives arises of curiosity about its function. Those matter should be a consideration by archaeologist when do next excavation and study, including the area which is supposed as an ancient settlement.